Determinants of Production of Agricultural Commodities of Food Crops in Bojonegoro Regency (Case Study of Farmers Accessing Tani Card and Non Accessing Tani Card) - Yuli Arma Andika (Kantor Perwakilan Bank Indonesia Provinsi Jawa Timur, 2021)
The Agricultural economy becomes an important issue in developing Bojonegoro’s Regen cy economy through the agriculture development program. Therefore, research dealing with the agriculture economy is still needed. This research aims to find out the influence of Labor, Land Area, Modal, fertilizer, and Farming Card to increase agriculture commodity production of crops in Bojonegoro Regency. This research uses quantitative descriptive research, the source of data used comes from primary data. The number of samples used in this research was 100 respondents. The technique of analyzing data was the ANCOVA method – multiple linear regression by using software Eviews 9. The results of the study showed simultaneously labor variables, land area variables, capital variables, fertilizer variables, and farming card variables had a significant effect and positively related to increased production of crop commodities. Partially, labor, land area, and capital significantly and positively correlated to the production of the crops. Meanwhile, fertilizer and Farming Card positively correlated but did not significantly influence the production of the crops. The Proportion of independent variable calculation explains the variance of crop production improvement in Bojonegoro Regency was 78.27%. Meanwhile, 21.28% explained by other variables outside the research. Thus, it is expected that the roles of related stakeholders to improve the agricultural economy.